The role of earning management as a mediator of the effect of the facial width to height ratio CEOs on leverage - Heru Tjaraka; Widi Hidayat; Rusdiyanto Rusdiyanto (Cogent Business & Management, 2022)
This study aims to prove the consistency of Agency Theory and Behavioral Consistency Theory as a solution to explain the role of Earnings Management in mediating the influence of male CEO masculinity on leverage. This research uses a quantitative approach with the population and research samples using companies on Indonesia’s Stock Exchange in 2014–2018. This study collected facial images identified as male CEOs from data from Indonesia’s Stock Exchange website and company websites and utilized Google searches. The data analysis method in this study uses Structural Equation Modeling (SEM) with Stata Software which connects theories, concepts and data that can be carried out on research variables. The findings explain that the decrease and increase in Earning Management practices has an impact on increasing and decreasing the value of the masculinity face of male CEOs also has an impact on increasing and decreasing the value of corporate leverage.